2015
DOI: 10.5194/npg-22-713-2015
|View full text |Cite
|
Sign up to set email alerts
|

Universal multifractal Martian topography

Abstract: Abstract. In the present study, we investigate the scaling properties of the topography of Mars. Planetary topographic fields are well known to roughly exhibit (mono)fractal behavior. Indeed, the fractal formalism reproduces much of the variability observed in topography. Still, a single fractal dimension is not enough to explain the huge variability and intermittency. Previous studies have claimed that fractal dimensions might be different from one region to another, excluding a general description at the pla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Multifractality Scaling allows us to introduce two distinct statistical processes : monofractal and multifractal. For a detailed description of the formalism we apply in this study, the readers can refer to Lovejoy and Shertzer (2013) briefly summed up in Landais et al (2015) . We now quickly recall the main notions here after.…”
Section: Statistical Momentsmentioning
confidence: 99%
“…Multifractality Scaling allows us to introduce two distinct statistical processes : monofractal and multifractal. For a detailed description of the formalism we apply in this study, the readers can refer to Lovejoy and Shertzer (2013) briefly summed up in Landais et al (2015) . We now quickly recall the main notions here after.…”
Section: Statistical Momentsmentioning
confidence: 99%
“…In our previous analysis (Landais et al, 2015), we performed the same kind of global analysis on the topographic data from Mars, from MOLA laser altimeter measurement (Smith et al, 2001). This analysis also find a good agreement with universal multifractal but on a restricted range of scale (Landais et al, 2015). Indeed the statistical structure has been found to be different at small scale (monofractal) and large scale (multifractal) with a transition occurring around 10 km.…”
Section: Universal Multifractalsmentioning
confidence: 67%
“…Multifractality M q allows us to introduce two distinct statistical structures of interest: monofractal and multifractal. For a detailed description of the formalism we apply in this study, the readers can refer to Lovejoy and Shertzer (2013) briefly summed in Landais et al (2015). We quickly recall the main notions here :…”
Section: Universal Multifractalsmentioning
confidence: 99%
“…Previous studies often found that a power law with an exponent −2.5 < b < −2 approximates the variance spectrum of topography well (Bills & Kobrick 1985;Balmino 1993;Ermakov et al 2018). At smaller scales, however, it is uncertain if a single power law can be an appropriate representation of topography (Landais et al 2015). Global data sets have limited resolution and the distribution of morphologies over the surface is inhomogeneous.…”
Section: Simulation Of Measurementsmentioning
confidence: 99%